Effectiveness of Combined Modern Dressing, Infrared, and Ozone Therapy on Diabetic Wound Healing: A Quasi-Experimental Study - Asni Hasaini; Muhlisoh Muhlisoh (PT.Mantaya Idea Batara, 2026)
Background: Diabetic ulcers are a long-standing problem of diabetes mellitus; in most cases, healing is challenging because of hyperglycemia, vasculopathy, or infection. The objective of this trial is to compare the therapeutic efficacy of a combination of modern dressings, infrared therapy, and ozone treatment with that of the conventional method in diabetic wounds. Methods: In terms of research design, a non-equivalent pretest-posttest quasi-experimental one-group/three-stage comparison was utilized. The sample included 30 participants, divided into two groups: 15 in the intervention group (modern dressing combined with infrared and ozone) and the rest in the control group receiving only modern dressing. Wound closure was assessed by the Bates-Jensen Wound Assessment Tool (BJAWT). The Wilcoxon and Mann-Whitney tests were used for statistical analysis. Results: The difference was significant in the intervention group but not in the control group. The between-group difference was also significant, with a medium effect size (0.715). The combined use of therapy exerted a synergistic effect, attributed to the preservation of wound moisture, the improvement of tissue perfusion and oxygenation, as well as a decline in bacterial count. Conclusion: It was suggested that integrating modern dressings, infrared, and ozone approaches can significantly promote tissue re-regulation in diabetic ulcer patients and should be considered a supplement therapy in wound nursing decisions.